Refining The Measurement of Individual Work Performance : A Discriminant Content Validity Approach - Yuditia Pramseswari; Markus Hartono; Frikson Christian Sinambela (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2026)
Individual Work Performance (IWP) is often considered one of the principal factors influencing the effectiveness of an organization, encompassing three principal components which are Task Performance, Contextual Performance, and Counterproductive Work Behavior. When employee work effectively and mentaly healthy, it will encourage flourishing in the workplace and improve organizational performance. Although individual work performance measurement instruments have been used several times, none have been able to capture all relevant aspects comprehensively. Hence, this research focused on assessing the relevance of adapted individual IWP items using Discriminant Content Validity (DCV). It involved the panel that consists of ten experts (n = 10) in several different categories such as psychometrician, researchers, state civil and professional industrial organizational psychologists. The expert panel evaluated the item-theory congruence for item alignment with dimensions and concepts. The findings showed the Intraclass Correlation Coefficient (ICC) values, ranging from 0.772 to 0.96, reflected strong inter-rater agreement and consistency in judgment. Also, one-sample t-tests on DCV estimates of all 18 items met the criteria of discriminant content validity. These findings offer meaningful implications for practitioners and researchers seeking to enhance performance assessment and foster well-being in organizational contexts Keywords: discriminant content validity, individual work performace, workplace wellbeing